2015
DOI: 10.1186/s12889-015-1363-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of adolescents’ cigarette smoking in Madinah, Saudi Arabia: a school-based cross-sectional study

Abstract: BackgroundAlthough the prevalence of adolescents’ cigarette smoking has increased in recent decades, little is known regarding its epidemiology in certain Saudi regions, including the Madinah region. The aim of this study was to determine the prevalence and predictors of adolescent cigarette smoking in Madinah, Saudi Arabia.MethodsA school-based cross-sectional study was carried out in the Madinah region during 2013. A multistage stratified cluster sample was taken and included 3400 students (11–19 years) from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
47
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 23 publications
9
47
0
3
Order By: Relevance
“…4,26 In a recent study, Figueiredo et al 16 observed that the prevalence of smoking in a sample of adolescents aged from 12 to 17 years was 5.7%, considering several Brazilian cities. Their findings were similar to those of the present study and their prevalence can also be considered low.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…4,26 In a recent study, Figueiredo et al 16 observed that the prevalence of smoking in a sample of adolescents aged from 12 to 17 years was 5.7%, considering several Brazilian cities. Their findings were similar to those of the present study and their prevalence can also be considered low.…”
Section: Discussionmentioning
confidence: 98%
“…To calculate the sample, the prevalence of smoking among adolescents was taken to be 15%, 4 and a tolerable error of 3% and power of 80% were used. Since the sample was selected through clusters, a design correction of 1.5 was used.…”
Section: Samplementioning
confidence: 99%
See 1 more Smart Citation
“…10 The peer pressure from smoker friends was among the most common reasons given for smoking among male secondary school students in Jeddah as it was stated that smoking friends and parents play an important role in the increased risk of smoking in the adolescents. 9,[11][12][13] …”
Section: Discussionmentioning
confidence: 99%
“…If the current trends continue the same, WHO expected that by 2030 tobacco smoking will kill more than 8 million of population worldwide each year (2,3). In addition, tobacco use causes hundreds of billions of dollars of economic damage worldwide each year (2,3),knowing that, the last prevalence of smokers was 37% which was estimated in Jeddah (4).In a school-based study conducted during 2013 among 3400 intermediate and secondary schools' students (11-19 years) in Madinah, Saudi Arabia using the global tobacco youth survey (GTYS) showed that prevalence of cigarette smoking was 15.17% (5).…”
Section: Introductionmentioning
confidence: 99%